2014
DOI: 10.1097/mbc.0b013e328364ba00
|View full text |Cite
|
Sign up to set email alerts
|

Association between prothrombin gene polymorphisms and hereditary thrombophilia in Xinjiang Kazakhs population

Abstract: To assess the association between polymorphisms of prothrombin gene and hereditary thrombophilia in Xinjiang Kazakhs population. Through cross-sectional investigation, permanent Kazakh population of Ili Kazakh Autonomous Prefecture was selected as the study object to measure their antithrombin III (AT-III), protein C, protein S activity and activated C protein resistance value, thus defining the situation of the crowd's hereditary thrombophilia. Sequenom Massarray detection technology was used to conduct a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The location and missense of the F2 variant suggest that it may exert an effect on the prothrombin function and destroy the vascular integrity during development and postnatal life (from the NCBI Reference Sequence Database). Previous research also observed the T165M variant located in F2 gene in the Xinjiang Kazakhs population, where it was associated with thrombophilia (17). …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The location and missense of the F2 variant suggest that it may exert an effect on the prothrombin function and destroy the vascular integrity during development and postnatal life (from the NCBI Reference Sequence Database). Previous research also observed the T165M variant located in F2 gene in the Xinjiang Kazakhs population, where it was associated with thrombophilia (17). …”
Section: Discussionmentioning
confidence: 68%
“…Following this filtration, only one variant (NM_000506:c.C494T:p.T165M;rs5896) was located in the candidate region. The variant is a homozygote missense mutation that has not previously been observed in Han Chinese population by other researchers, but this variant was reported as a genetic risk factor associated with thrombophilia in the Xinjiang Kazakh population (17). …”
Section: Resultsmentioning
confidence: 88%
“…There are few studies concerning Thr165Met published so far. However, authors report that it is a genetic marker of thrombophilia, and even in heterozygous form it is also associated with the risk for venous thrombosis [ 30 , 31 ]. These works report on family thrombosis in patients who are both homo- and heterozygous for the Thr165Met mutation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of our family study, the proband’s mother carried c.494C > T (p.Thr165Met), which is thought to be related to Xinjiang Kazakh thrombotic disease ( Ge et al, 2014 ) and may play a role in kidney stone disease ( Rungroj et al, 2012 ). However, the association of this mutation with Xinjiang Kazakh thrombotic disease may be the result of the interaction of genes and complex environmental factors.…”
Section: Discussionmentioning
confidence: 99%